-120(x+20)2x=200

Simple and best practice solution for -120(x+20)2x=200 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -120(x+20)2x=200 equation:


Simplifying
-120(x + 20) * 2x = 200

Reorder the terms:
-120(20 + x) * 2x = 200

Reorder the terms for easier multiplication:
-120 * 2x(20 + x) = 200

Multiply -120 * 2
-240x(20 + x) = 200
(20 * -240x + x * -240x) = 200
(-4800x + -240x2) = 200

Solving
-4800x + -240x2 = 200

Solving for variable 'x'.

Reorder the terms:
-200 + -4800x + -240x2 = 200 + -200

Combine like terms: 200 + -200 = 0
-200 + -4800x + -240x2 = 0

Factor out the Greatest Common Factor (GCF), '-40'.
-40(5 + 120x + 6x2) = 0

Ignore the factor -40.

Subproblem 1

Set the factor '(5 + 120x + 6x2)' equal to zero and attempt to solve: Simplifying 5 + 120x + 6x2 = 0 Solving 5 + 120x + 6x2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. 0.8333333333 + 20x + x2 = 0 Move the constant term to the right: Add '-0.8333333333' to each side of the equation. 0.8333333333 + 20x + -0.8333333333 + x2 = 0 + -0.8333333333 Reorder the terms: 0.8333333333 + -0.8333333333 + 20x + x2 = 0 + -0.8333333333 Combine like terms: 0.8333333333 + -0.8333333333 = 0.0000000000 0.0000000000 + 20x + x2 = 0 + -0.8333333333 20x + x2 = 0 + -0.8333333333 Combine like terms: 0 + -0.8333333333 = -0.8333333333 20x + x2 = -0.8333333333 The x term is 20x. Take half its coefficient (10). Square it (100) and add it to both sides. Add '100' to each side of the equation. 20x + 100 + x2 = -0.8333333333 + 100 Reorder the terms: 100 + 20x + x2 = -0.8333333333 + 100 Combine like terms: -0.8333333333 + 100 = 99.1666666667 100 + 20x + x2 = 99.1666666667 Factor a perfect square on the left side: (x + 10)(x + 10) = 99.1666666667 Calculate the square root of the right side: 9.958246164 Break this problem into two subproblems by setting (x + 10) equal to 9.958246164 and -9.958246164.

Subproblem 1

x + 10 = 9.958246164 Simplifying x + 10 = 9.958246164 Reorder the terms: 10 + x = 9.958246164 Solving 10 + x = 9.958246164 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = 9.958246164 + -10 Combine like terms: 10 + -10 = 0 0 + x = 9.958246164 + -10 x = 9.958246164 + -10 Combine like terms: 9.958246164 + -10 = -0.041753836 x = -0.041753836 Simplifying x = -0.041753836

Subproblem 2

x + 10 = -9.958246164 Simplifying x + 10 = -9.958246164 Reorder the terms: 10 + x = -9.958246164 Solving 10 + x = -9.958246164 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = -9.958246164 + -10 Combine like terms: 10 + -10 = 0 0 + x = -9.958246164 + -10 x = -9.958246164 + -10 Combine like terms: -9.958246164 + -10 = -19.958246164 x = -19.958246164 Simplifying x = -19.958246164

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.041753836, -19.958246164}

Solution

x = {-0.041753836, -19.958246164}

See similar equations:

| 0.2(x+3)=1.6 | | 5x-5=2(3x-1)-2(x+3) | | 5x-5=6x-2-2x+6+7 | | -5y-1/6=7/5 | | 8(3x-7)=-6(x-7)+4 | | -5y-1/6=12/5 | | 3x-2x+8=x+4x | | 4(-2-3x)=-[6x-5(8-6x)] | | 3x+12=4x-10+13 | | (7+2i)(2-5i)= | | 4(-2.3x)=-[6x-5(8-6x)] | | 1.4x-2.8=-7 | | 0=3x^2-1x-44 | | m6/m2 | | 5x^4-9x^3+3x^2+x=0 | | -10-5n=25 | | 4N+5-13=3.4 | | 12-4x+2=5x+1 | | 7w+46=-3(w+8) | | -7-5r=73 | | 8n-7=129 | | 6N+8(N+15)=11.70 | | -9.5=1.9x-19 | | 6N+8(N+5)=11.70 | | 10-6a=52 | | -9.5=1.9-19 | | 2*(x-3)=3x | | 8N+6-7=308 | | -4x=-(x-8) | | 12/13x^-1/13-25/13x^12/13=0 | | 2x-4y=y+12 | | 2N+3-5=45 |

Equations solver categories